(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In the workplace, sexual harassment undermines gender equality, leads to discriminatory hiring practices, and negatively influences employees’ dignity and well-being. Sexual harassment is a kind of sex discrimination. If ignored, it can result in substantial expenses for businesses due to productivity loss, low worker morale, absenteeism, and employee turnover. It causes psychological anguish and stress for victiMs. With a few notable exceptions, investigations into workplace sexual harassment have been conducted primarily in developed nations. Even in affluent nations where workplace sexual harassment has been thoroughly examined, empirical research has not produced conclusive results about its causes and effects, both personally and organizationally. Studies have shown that even small acts of sexual harassment, such as making obscene remarks or making the hottest jokes, over time can result in severe psychological discomfort. The perceived aspect of workplace sexual harassment is a significant issue. There may be differences between what sexual harassment is to men and women. Given that men regarded fewer activities as sexual harassment in his study. According to Champlin K. Oldham (2019), sexual harassment refers to unwelcome sexual advances, comments of a sexual nature, requests for sexual favors, and harassment or comments about an individual’s gender, all of which create a hostile work environment. Most commonly, sexual harassment is perpetrated by someone in a position of authority over the victim, such as an employer, supervisor, or teacher. Sexual harassment attacks no sexual orientation. It can be experienced by both males and females in any form in any working environment; sexual harassment is not only a physical crime against women and men but has been found responsible for their poor physical and emotional health. Have reported that sexual harassment can have negative academic, psychological, and behavioral impacts on the victim. Sexual harassment affects the mental health of both genders. Sexual harassment can cause low self-esteem, post-traumatic syndrome (PTSD), anxiety, depression, and sexual dysfunction. Sexual harassment happens in the working environment. The employer commits sexual violence to their employee in exchange for a promotion or any other position in a company. Women and men experience sexual harassment in their working environment. Women are discriminating against their gender, and it will cause them to quit their jobs to avoid any form of sexual harassment. Men have experienced this sexual harassment in their working environment by their male bosses. They will touch and caress their thighs or their arm or whisper to their ears some sexual statement. This research determines the negative impact of sexual harassment on every individual in our society. The researchers answered the question: what is the assistance made by the company or local authorities to the employees who are victims of sexual harassment in Valenzuela city? Rank one, “.Advice or options available before filing the complaint.” With a mean score of 2.50, it is interpreted as partially Agreeable. Rank two, “.Referral to an agency offering professional help,” with the same mean score of 2.50, interpreted as partially Agreeable. Rank three,” Giving counseling to the victim of the harassment,” with the same mean score of 2.50, interpreted as Partially Agree. Rank four, “Action is taken to address the concerns raised, potential including training and discipline.” with a total mean score of 2.50 interpreted Partially Agree.